Effect of mind sound resonance technique on physiological and psychological parameters among geriatric population: a structured study protocol for a randomized controlled trial - S., Prashanth; V., Nalini; S., Priyanka; J., Thanalakshmi; V., Subbulakshmi; A., Amalraj; K., Maheshkumar (International Journal of Clinical Trials, 2024)
Background: Aging involves physical, psychological, and social changes, including chronic non-communicable pathologies and HPA axis dysfunction. Yoga can manage these issues, while mind sound resonance technique (MSRT) can alleviate stress, anxiety, and improve psychomotor function. This study aims to report the methodology for three months of MSRT sessions and their impact on physiological and psychological parameters in the geriatric population. Methods: A randomized controlled trial will involve 80 participants aged 60-75 years, divided into an intervention group and a control group. The intervention group will receive 45 minutes of MSRT sessions daily for 90 days, while the control group will not receive any intervention. Post-intervention assessment will be taken and compared with the control group after 90 days. Conclusions: MSRT, having a dual benefit as meditative and relaxation component, has been shown to improve the physiological and psychological well-being of the geriatric population, with expected outcomes including improved cardio-autonomic, pulmonary, neurocognitive, and psychological functions and changes in serum stress markers. Trial registration (CTRI): CTRI/2024/02/062308.